Can Destination Therapy be implemented in children with heart failure? A study of provider perceptions. (29th June 2016) - Char, Danton S.; Lee, Sandra S.‐J.; Ikoku, Alvan A.; Rosenthal, David; Magnus, David
Abstract: DT is an established final therapeutic choice in adult patients with severe heart failure who do not meet criteria for cardiac transplantation. Patients are given VADs, without the prospect of care escalation to transplantation. VADs are now established therapy for children and are currently used as a bridge until transplantation can be performed or heart failure improves. For children who present in severe heart failure but do not meet transplantation criteria, the question has emerged whether DT can be offered. This qualitative study aimed to elicit the perspectives of early adopters of DT at one of the few institutions where DT has been provided for children. Responses were recorded and coded and themes extracted using grounded theory. Interviewees discussed: envisioning of the DT candidate; approach to evaluation for DT; contraindications to choosing DT; and concerns about choosing DT. Providers articulated two frameworks for conceptualizing DT: as a long bridge through resolution of problems that would initially contraindicate transplantation or, alternatively, as a true destination instead of transplantation. True destination, however, may not be the lasting concept for long‐term VAD use in children given improvement in prognosis for current medical contraindications and improving VAD technology.